Library wars. 13. Love & war. - Yumi, Kiiro (Shojo beat manga., 2015)
In the near future, the federal government creates a committee to rid society of books it deems unsuitable. The libraries vow to protect their collections, and with the help of local governments, form a military group to defend themselves--the Library Forces! The Media Betterment Committee has silenced a famous writer, and Library Forces member Iku Kasahara and her supervisor and secret crush, Dojo, must fight to protect his right to speak...and live! As the Library Forces wage a fierce battle against censorship, Iku and Dojo's burgeoning relationship provides the team with a welcome distraction, and--unfortunately for them--some comic relief!